2000
DOI: 10.1039/a908469j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) chloride complexes with 1,2,4-triazolo[1,5-a]pyrimidines: X-ray, 15N–1H NMR and 15N CP MAS studies

Abstract: The crystal structure of [Pd(dbtp) 2 Cl 2 ]ؒ0.5 C 2 H 5 OH 4c was resolved by X-ray diffraction analysis, exhibiting monomeric, nearly square-planar cis geometry and N(3) co-ordination. A small tetrahedral distortion from the co-ordination plane was observed. The Pd-Cl distances are 2.276(1) and 2.283(1) Å, and Pd-N 2.042(3) and 2.040(3) Å. Spectroscopic measurements (UV-VIS, IR, NMR) suggested analogous structures for 1, 2 and 3. Compounds 4a and 4b are most likely rotational isomers in solution and distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
(43 reference statements)
8
26
0
Order By: Relevance
“…As shown in Table 3, the NH 2 cytosine protons of cis-[PdCl 2 (Gua)(Cyt)] which are directly adjacent to the coordinating N3 ring nitrogen show a downfield shift from 7.06 to 7.70 ppm in the complex. Similarly, the NH 2 protons of guanine observed in the free ligand at 5.57 ppm was shifted to 5.95 ppm showing that these protons experienced strong deshielding effects upon complexation [37]. Similar chemical shifts were observed for the remaining protons as shown in Table 3.…”
Section: 5supporting
confidence: 65%
See 1 more Smart Citation
“…As shown in Table 3, the NH 2 cytosine protons of cis-[PdCl 2 (Gua)(Cyt)] which are directly adjacent to the coordinating N3 ring nitrogen show a downfield shift from 7.06 to 7.70 ppm in the complex. Similarly, the NH 2 protons of guanine observed in the free ligand at 5.57 ppm was shifted to 5.95 ppm showing that these protons experienced strong deshielding effects upon complexation [37]. Similar chemical shifts were observed for the remaining protons as shown in Table 3.…”
Section: 5supporting
confidence: 65%
“…respectively [37]. These transitions confirm the square planar (D 4h ) geometry of the Pd(II) ion [31].…”
Section: Electronic Absorption Spectra Conductivity and Magneticsupporting
confidence: 59%
“…The IR spectra of the complexes have been examined in comparison with the spectra of the free ligands [33]. The two most characteristic bands in the IR spectra of dbtp and dptp, assigned to an overall triazolopyrimidine and pyrimidine ring mode vibrations, ν tp (1615 and 1612 cm − 1 ) and ν py (1530 and 1543 cm − 1 ), are generally moved to higher frequencies in transition metal complexes [34,35].…”
Section: Ir Spectra and Mössbauer Datamentioning
confidence: 99%
“…1) is recognized as the main coordination behaviour of tp and dmtp [1]. It has been observed that the coordination of metal ions through N(3) results in a shift of m tp and m py bands, assigned to triazolopyrimidine and pyrimidine ring mode vibrations, respectively, usually towards higher frequencies [11][12][13][14][15][16][17][18]. The shifts observed in the spectra of our complexes, reported in Table 1, are consistent with N(3) coordination of the organotin(IV) 2 points out that this compound assumes a lower symmetry structure (see Table 2).…”
Section: Solid State Structures Of the Adductsmentioning
confidence: 99%